2014
DOI: 10.3389/fnint.2014.00084
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic fields as structure-function zeitgebers in biological systems: environmental orchestrations of morphogenesis and consciousness

Abstract: Within a cell system structure dictates function. Any interaction between cells, or a cell and its environment, has the potential to have long term implications on the function of a given cell and emerging cell aggregates. The structure and function of cells are continuously subjected to modification by electrical and chemical stimuli. However, biological systems are also subjected to an ever-present influence: the electromagnetic (EM) environment. Biological systems have the potential to be influenced by subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 67 publications
1
29
0
Order By: Relevance
“…This theory can be cast as a vertex-resumed kinetic theory and it has been indicated that the IR dynamics are a nonrelativistic system, where a self-interacting scalar field exhibits IR dynamics, reminiscent of turbulent nonrelativistic superfluids in 3+1-dimensions (Berges, 2015). Some of the life frequencies found by us are also reported by Rouleau and Dotta (2014) and are numerically fully in line with our present data.…”
Section: Electromagnetic Signaling Properties Of Clay Under Quantum Csupporting
confidence: 81%
“…This theory can be cast as a vertex-resumed kinetic theory and it has been indicated that the IR dynamics are a nonrelativistic system, where a self-interacting scalar field exhibits IR dynamics, reminiscent of turbulent nonrelativistic superfluids in 3+1-dimensions (Berges, 2015). Some of the life frequencies found by us are also reported by Rouleau and Dotta (2014) and are numerically fully in line with our present data.…”
Section: Electromagnetic Signaling Properties Of Clay Under Quantum Csupporting
confidence: 81%
“…EMF's (electromagnetic fields) can be located externally, but also be present internally in living organisms, for instance being induced by ion-fluxes of Na+, K+ and Ca2+ (see McFadden, 2007;Pockett, 2012;Rouleau, 2014;Pereira, 2011). There are plausible models that indicate that DNA itself can function as an aggregate of EM antennae that could discern, differentiate, and transform EM energies to perturbations in basepair sequences (Cosic, 1994;Mihai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…If each neuron were discharging within the theta band, this would be equivalent to between 1 million to 10 million neurons. This range has been associated with the critical number associated with a "percept" or experience (Rouleau and Dotta, 2014), and, is equivalent to the numbers of primary neurons within the human hippocampal formation (Gloor, 1997).…”
Section: Discussionmentioning
confidence: 99%